Aspectos estratégicos da expatriação a partir da abordagem da estratégia como prática social - Soares, Raquel Santos (2008)
This work it based on an emergent approach, in which strategy is considered a social practice, to analyze a practice that has become common in companies located in Brazil - the expatriation. To send professionals abroad respond pressing organizational need - due the fact of that each time more companies have been launched to the international expansion of its operations. From the point of view of the individual who expatriates, the experience in the exterior can assume different "strategic" connotations, from the improvement of a language to the understanding of the cultural diversity, also valued for the companies whom internationalize. In the organizational studies, authors of the strategy as social practice have turned themselves toward the actions of the people involved in "making strategy", or either, for the agreement of as the strategists or practitioners execute the practice of strategizing, analyzing the interaction between them, and of them with the physical and social resources - the practices - available in certain cultural-historic context. The methodological approach for understanding of the objective aspects of the expatriation, on the part of the company, and subjective, on the part of the professional who lives deeply this experience, uses the concepts of field, capital and habitus of Pierre Bourdieu, that it is one of the authors of sociology that had influenced the "practice turn ", this means, a movement for the understanding the practice of the human activities. The objective of this proposal is to analyze the role of the practice of expatriation in conciliating objective aspects of the company who sends the expatriated one, and subjective, leading in account the interests of the individual who expatriates. In the approach of strategy as social practice, the practice of strategy depends on who is these strategists, not only in terms of their qualifications and professional experiences, but also of personal experiences that bring to play their roles and of the interests that they search. Unmasking the organizational field and practical of expatriation return for the understanding of the objective aspects of the companies in sending professionals abroad; the analysis of the capital forms makes possible to advance in the agreement of interests of the professionals who promote this practice, as much in terms of economic, cultural and social valuation, how much of symbolic value. Habitus, in turn, discloses that it has certain recondite intentionality in the trajectory of the interviewed professionals, whom they had accepted as challenge the idea of living in another country, in some cases, with their family. Throughout the narratives, it can be verified that the expatriation approaches to a social practice, once makes possible to the expatriated live deeply exclusive situations, due its direct contact with a different reality, giving a new vision on its work here in Brazil, mainly when this continues related to the delivery of dependent strategic results of international operations. The narratives had been analyzed by the technique of Critical Analysis of Speech, that it makes possible to extend the understanding of interviewed speeches for "the fondness to say even though" and for "not saying", disclosing how much of themselves they loan to the execution of a strategic activity for the organization in which work.